Implementasi Prophet Forecasting Model Dalam Prediksi Kualitas Udara Daerah Istimewa Yogyakarta - Oktavia, Feliana; Witanti, Arita (Universitas Multi Data Palembang, 2024)
Air is essential for the life of living things, immaculate air. Air needs to be measured at all times to determine the quality it contains. In the Yogyakarta area, air quality is measured by the Yogyakarta City Environmental Agency and documented in an index called the Air Pollutant Standard Index or ISPU. ISPU can be used to assist the government in taking steps and policies toward air quality control as well as predicting air quality in the future. Prediction or forecasting can be done using the Prophet model with data collection and problem-solving using the model. The forecasting results with the Prophet model found very accurate results with an MAE value of 0.4354644200045299, MAPE of 0.81%, MSE of 0.32, and RMSE of 0.56.